Change lost: Corrosion of Roman copper alloy coins in changing and variable burial environments. (February 2023) - Huisman, Hans; Ackermann, Regula; Claes, Liesbeth; van Eijck, Lambert; de Groot, Tessa; Joosten, Ineke; Kemmers, Fleur; Kerkhoven, Nils; de Kort, Jan-Willem; Lo Russo, Sarah; Ngan-Tillard, Dominique; van Os, Bertil; et al.
Highlights: Study of copper alloy coin corrosion in changing and variable environments. Exchange of Cu for Fe under fluctuating redox conditions, potentially causing classification of massive coins as subferrati . Cu sulphides and gypsum replace metallic copper in coastal acidic conditions. Alkaline conditions in fire remains cause strong leaching of copper. Coins corrode anisotropically, resulting in strong lamination. Abstract: We studied the corrosion of Roman copper alloy coins that experienced alternations or progressive changes in their burial environment. We used coins that were still embedded in soil or in a concretion selected from three professional excataved sites - Berlicum and Krommenie in the Netherlands and Kempraten in Switserland. mCT scanning and neutron scanning were used to record the 3-D properties of these coins prior to (destructive) analyses. It proved possible to tentatively identify the coins. Microscope observations and SEM-EDX analyses revealed complex corrosion processes, related to changing burial environments. In soil horizon with fluctuating groundwater levels in a region with upwelling reducing, iron-rich groundwater, the copper in a gunmetal coin is essentially replaced by iron oxides while tin remains and forms tin-oxide bands. Fluctuating redox conditions in marine-influenced environments was shown to transform a copper-alloy coin into strongly laminated copper sulphides with embedded gypsum crystals, with an outer surface of copper and copper-iron sulphides. Burial of bronze in a charcoal rich layer probably caused temporary highly alkaline soil conditions. This caused most of the copper to leach from this coin, leaving behind a laminated tin-dominated mass, with only a limited amount of (malachite) corrosion products remaining in the surrounding groundmass. In all three cases, corrosion processes tend to be anisotropic, probably because of cold-hammering of the coins during their manufacture. Such corrosion processes on massive copper alloy coins may produce features that may lead to their incorrect classification as subferrati, i.e. copper alloy coins with an iron core. Our results may help in future to distinguish strongly corroded massive coins from subferrati .